Sea Floor Exploration Scientific Adventures Diving into the Abyss - Hekinian, Roger (Springer Oceanography, 2014)
The author participated in 38 sea going expeditions including the first manned-submersible project to explore the Mid-Atlantic Ridge. This book provides a comprehensive overview of the past 45 years of sea floor exploration. It summarizes the mineralogical and petrological composition of sea floor rocks, ocean floor volcanism in relation to the geological setting and the discovery of hydrothermal activity related to metalliferous deposits. Topics covered include the creation of the sea floor, its fracture zones and the structural setting of subduction zones In addition to learning about various scientific missions and their objectives, the reader is introduced to rift zones where the sea floor is being created, as well as to fracture zones, intraplate volcanoes, and the structural setting of subduction zones.      .